2005
DOI: 10.1016/j.ydbio.2004.11.035
|View full text |Cite
|
Sign up to set email alerts
|

FGFR3 regulates brain size by controlling progenitor cell proliferation and apoptosis during embryonic development

Abstract: Mice with the K644E kinase domain mutation in fibroblast growth factor receptor 3 (Fgfr3) (EIIa;Fgfr3(+/K644E)) exhibited a marked enlargement of the brain. The brain size was increased as early as E11.5, not secondary to the possible effect of Fgfr3 activity in the skeleton. Furthermore, the mutant brains showed a dramatic increase in cortical thickness, a phenotype opposite to that in FGF2 knockout mice. Despite this increased thickness, cortical layer formation was largely unaffected and no cortical folding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 64 publications
5
55
0
Order By: Relevance
“…Interestingly, inactivation of these FGFRs sustains a compartment of self-renewing GLAST ϩ MPNSCs whose survival may instead depend on epidermal growth factor and its receptors, which are expressed by a small fraction of cortical NSCs at E13 (Maric et al, 2003). Together, our findings emphasize the critical role of bFGF/FGFR signaling during the onset of neurogenesis in the rat cortex, and may explain the results obtained with transgenic mice and other in vitro studies that have demonstrated critical roles for bFGF and FGFRs in the expansion of NEPs, including putative NSCs and/or neural progenitors (Qian et al, 1997;Vaccarino et al, 1999;Raballo et al, 2000;Korada et al, 2002, Shin et al, 2004Inglis-Broadgate et al, 2005;Fortin et al, 2005). However, the identities of the earliest-born neurons derived from GLAST Ϫ NSCs and GLAST ϩ NSCs as putative pioneer neurons and Cajal-Retzius neurons, which emerge at the beginning of neurogenesis in the rat (Meyer et al, 1998), remain to be established.…”
Section: Complex Bfgf/fgfr Signaling Mediates the Plasticity Of Nscssupporting
confidence: 64%
“…Interestingly, inactivation of these FGFRs sustains a compartment of self-renewing GLAST ϩ MPNSCs whose survival may instead depend on epidermal growth factor and its receptors, which are expressed by a small fraction of cortical NSCs at E13 (Maric et al, 2003). Together, our findings emphasize the critical role of bFGF/FGFR signaling during the onset of neurogenesis in the rat cortex, and may explain the results obtained with transgenic mice and other in vitro studies that have demonstrated critical roles for bFGF and FGFRs in the expansion of NEPs, including putative NSCs and/or neural progenitors (Qian et al, 1997;Vaccarino et al, 1999;Raballo et al, 2000;Korada et al, 2002, Shin et al, 2004Inglis-Broadgate et al, 2005;Fortin et al, 2005). However, the identities of the earliest-born neurons derived from GLAST Ϫ NSCs and GLAST ϩ NSCs as putative pioneer neurons and Cajal-Retzius neurons, which emerge at the beginning of neurogenesis in the rat (Meyer et al, 1998), remain to be established.…”
Section: Complex Bfgf/fgfr Signaling Mediates the Plasticity Of Nscssupporting
confidence: 64%
“…This has been shown in mice with a gain-of-function mutation of FGFR3 (Inglis-Broadgate et al, 2005). The alternative possibility-a direct increase in neuroblasts without an effect on proliferating cell survival-has been observed in transgenic mice expressing a stabilized form of ␤-catenin (Chenn and Walsh, 2002).…”
Section: Early Neural Cell Death Is Also Associated With Neurogenesismentioning
confidence: 96%
“…In humans, increased surface area and precocious formation of supernumerary gyri occur in thanatophoric dysplasia, a genetic disorder caused by activating mutations of fibroblast growth factor receptor 3 [53] . In a mouse model of thanatophoric dysplasia, the expansion of cortical surface area was linked to excessive proliferation of radial unit progenitors before E12.5 [54] .…”
Section: The Intermediate Progenitor Hypothesis and Radial Unit Hypotmentioning
confidence: 99%